Model based on TPM to increase the overall efficiency of equipment in an oil company (LACCEI, 2024)
The palm oil industry accounts for 33% of vegetable oil production worldwide and has seen an increase in demand in recent years. Despite this, demand in Peru cannot be met because, in many companies, the efficiency of the machines is far below the ideal indicator of 85%. In the company under study, located in the Ucayali-Peru region, the overall equipment efficiency (OEE) is 73.27%, implying that the machinery is not adequately utilized. In that sense, this article shares a real experience of the palm oil industry for an improvement project evaluated with the OEE indicator through the Total Productive Maintenance (TPM), Single-Minute Exchange of Die (SMED) methodologies, among other engineering tools. The final objective is to achieve an improvement in the OEE metric up to the World-Class category of 85%. After simulating the proposed model in Arena taking as indicators the MTTR, Set-up time and downtime, a new improved OEE was calculated, which meant an increase of 14.97%, with an availability of 2.96% and a yield of 12.59%. The verdicts of this labor exposed the profit of TPM application in real world oil companies.